2021
DOI: 10.1371/journal.pone.0259658
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurses’ behavioral intention toward caring for COVID-19 patients on mechanical ventilation: A cross-sectional study

Abstract: Objectives To investigate nurses’ behavioral intention toward caring for COVID-19 patients on mechanical ventilation, as well as the factors affecting their intention. Background COVID-19 patients undergoing mechanical ventilation have many care needs and pose more challenges for nurses, which might adversely affect nurses’ intention toward caring behavior. Methods A cross‐sectional study was conducted by using simple random sampling to recruit 598 nurses from five tertiary hospitals in Sichuan Province, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
0
19
0
1
Order By: Relevance
“…The identified barriers to providing frontline care included safety concerns, family–work conflict, inadequate organisational support and social stigma (Ke et al, 2021 ; Luo et al, 2021 ; Wu et al, 2020 ). Conversely, a strong professional identity (Cheng et al, 2021 ), positive psychological capital (Jeong & Kim, 2022 ) and job satisfaction (Sharif Nia et al, 2021 ) served as enablers of nurses' work motivation. Moreover, prior qualitative research demonstrated that nurses' perceptions of ethical challenges in caring for COVID‐19 patients adversely affected their willingness to engage in frontline activities (Alloubani et al, 2021 ; Rezaee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified barriers to providing frontline care included safety concerns, family–work conflict, inadequate organisational support and social stigma (Ke et al, 2021 ; Luo et al, 2021 ; Wu et al, 2020 ). Conversely, a strong professional identity (Cheng et al, 2021 ), positive psychological capital (Jeong & Kim, 2022 ) and job satisfaction (Sharif Nia et al, 2021 ) served as enablers of nurses' work motivation. Moreover, prior qualitative research demonstrated that nurses' perceptions of ethical challenges in caring for COVID‐19 patients adversely affected their willingness to engage in frontline activities (Alloubani et al, 2021 ; Rezaee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ajzen ( 2011 ), the TPB is most appropriate for predicting behaviours that are beyond one's volitional control, as is the case of caring for patients with emerging infectious diseases. Indeed, previous studies have used this model to explain up to 55% of variance in nurses' and student nurses' intention to provide care in the contexts of COVID‐19 (Cheng et al, 2021 ; Minuye et al, 2021 ; Tran et al, 2021 ), SARS (Ko et al, 2004 ), H1N1 (Jeong et al, 2015 ) and emerging infectious diseases (Lee & Kang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our survey showed that 69.12% of nurses were willing to care for patients with COVID-19 and 75.58% had a positive attitude. This may be related to the professional responsibilities and ethical cognition of nurses ( 21 ). Both the multiple regression analysis and structural equation model results indicated that attitude had the greatest influence on behavioral intentions, indicating that the more positive the behavioral attitude, the stronger the behavioral intentions.…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese study conducted in February 2020, 83.4% of nurses were willing to provide patient care in the Wuhan region (Gan et al, 2020 ). From November to December of the same year, 94.7% of nurses were willing to provide care for severely ill COVID‐19 patients on mechanical ventilation (Cheng et al, 2021 ). In Korea, a study conducted in September 2020 reported a rate of 55.4% for intent to provide COVID‐19 care (Kyung & Shin, 2021 ).…”
Section: Discussionmentioning
confidence: 99%